Practical questions on farm management - Doane, Lawrence A. (My University, 1904)
Introduction: The study of Farm Management having been introduced into the agricultural course of the Kansas State Agricultural College, it was decided by Professor TenEyck who has this branch of study in charge, that some of the methods of farm management employed by the farmers over the state, and by the farmers of other states might be studied with advantage, providing that the plan of the methods employed could be secured. With this object in view the names of prominent farmers were sought and procured, both in this state and in other states. The 1904 class in this subject, acting with the professor, then made up a list of questions which were submitted to the farmers for answer. This list of questions was sent to nearly two-hundred farmers with a letter explaining the purpose of the investigation, and requesting careful and concise answers. As a result, in the neighborhood of fifty of the men addressed, answered the questions more or less fully. I was appointed by professor TenEyck to work up the data secured and I have sought to put the answers into a form so that their contents may be noted easily. Such answers should be of value and interest to farmers generally, as showing the methods whereby some men out of the many engaged in agriculture throughout the United States, have carried on their farming business successfully, and by successfully I mean profitably.
An investigation of farm management
Citation: Doane, Lawrence A. Practical questions on farm management. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Farm Management; Farming Techniques; Farmers; Theses